Mendengarkan Murottal Al Quran terhadap Kualitas Tidur Pasien Gangguan Pola Napas - Maya Ardilla Siregar; Nurhannifah Rizky Tampubolon; Ani Rahmadhani Kaban (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the effectiveness of listening to the murottal Al Quran on the sleep quality of patients with impaired breathing patterns in the Inpatient Room Floor III Lung Mitra Medika Hospital, Tanjung Mulia. This research method uses a quasi-experimental post-pre test. The results showed that the majority of patients with impaired breathing patterns in the Lung III inpatient room at Mitra Medika Tanjung Mulia General Hospital were aged 51-60 years with a percentage of 40.6%, 22 male sex (68.8%), last high school education history 15 people 46.9%, 16 people (50%) have Batak ethnicity, the married status of 24 respondents with a percentage of 75.0%, with a medical diagnosis of the majority of pulmonary TB as many as ten respondents (31.3%), There are 11 private employees with employment history (34.4%) and all respondents experienced poor sleep quality with a percentage of 100%. In conclusion, listening to the murottal Koran affects the sleep quality of patients with impaired breathing patterns in the inpatient room of RSU Mitra Medika Tanjung Mulia. Keywords: Disturbance of Breathing Patterns; Sleep Quality; Murottal Al Quran